2014
DOI: 10.1007/s13197-014-1687-x
|View full text |Cite
|
Sign up to set email alerts
|

Improving the color of bulgur: new industrial applications of tempering and UV/sun-light treatments

Abstract: Color (CIE b*; yellowness) is an important parameter for bulgur quality. Color of bulgur is mainly due to natural pigments (carotenoids) that are present at different levels in wheat. In order to increase the customer acceptability, the producers try to obtain yellowish color in bulgur. In this study, two different tempering methods (spray and steam) were used before sun and UV-light polishing applications. Sun and UVlight were applied to tempered bulgur for 12, 24, 36, 48, 60 and 72 h. Moisture content (%, d.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Although there are many studies related to color of bulgur in the literature (Bayram & Oner, 2006;Hayta, 2002;Kahyaoglu, Sahin, & Sumnu, 2010), the lack of studies on carotenoid content, which has the greatest effect on color, draws attention. In one of the existing studies, Balci and Bayram (2015) investigated the effect of different tempering processes (spray steam) and polishing methods (sun light-UV light) with 0-72 hr on the TCC of the bulgur. They reported that the TCC of the samples was between 3.65 and 6.31 µg/g and the best method in terms of TCC was provided in the combination of spray tempering and UV light polishing.…”
Section: Total Carotenoid Contentmentioning
confidence: 99%
“…Although there are many studies related to color of bulgur in the literature (Bayram & Oner, 2006;Hayta, 2002;Kahyaoglu, Sahin, & Sumnu, 2010), the lack of studies on carotenoid content, which has the greatest effect on color, draws attention. In one of the existing studies, Balci and Bayram (2015) investigated the effect of different tempering processes (spray steam) and polishing methods (sun light-UV light) with 0-72 hr on the TCC of the bulgur. They reported that the TCC of the samples was between 3.65 and 6.31 µg/g and the best method in terms of TCC was provided in the combination of spray tempering and UV light polishing.…”
Section: Total Carotenoid Contentmentioning
confidence: 99%
“…During spraying, the wheat kernels were mixed. After the tempering [11], the samples were left for 15 min (tempering time).…”
Section: Temperingmentioning
confidence: 99%
“…According to Balci and Bayram [11], a mechanical polishing system was used (Lab. Scale Mechanical/Kneading/ polisher, Biltek Eng., Gaziantep/Turkey).…”
Section: Screeningmentioning
confidence: 99%
“…After milling, an additional polishing step of tempered (~17%) bulgur can be added in order to increase the bright yellow color of the bulgur and therefore its market competiveness (Balcı & Bayram, 2015). A mechanical polisher kneads, or squeezes, the bulgur making it smoother and heat is generated through friction aided by the electrical heater of the polisher (Balcı & Bayram, 2015). The bulgur can be steam tempered or spray tempered before polishing although steam tempering has been shown to be more effective at increasing the b* color values.…”
Section: Production and Processingmentioning
confidence: 99%